Enhancing the Freeze–Thaw Durability of Concrete through Ice Recrystallization Inhibition by Poly(vinyl alcohol) - Qu, Zhengyao (ACS Omega, 2020)
[Image: see text] Frost weathering of porous materials caused by seasonal temperature changes is a major source of damage to the world’s infrastructure and cultural heritage. Here we investigate poly(vinyl alcohol) (PVA) addition as a means to enhance the freeze–thaw durability of concrete without compromising its structural or mechanical integrity. We evaluate the ice recrystallization inhibition activity of PVA in a cementitious environment and the impact of PVA on key structural and mechanical properties, such as cement hydration (products), microstructure, strength, as well as freeze–thaw resistance. We find that a low amount of PVA significantly reduces the surface scaling of concrete and displays excellent ice recrystallization inhibition in the saturated Ca(OH)(2) solution, which has a similar pH value as cement pore solution, while it does not affect cement hydration, microstructure, nor its mechanical properties. These findings contribute to new insights on the freeze–thaw damage mechanism, and more importantly, we disclose a new direction for the design of concrete with excellent freeze–thaw resistance.